KAPASITAS PEMERINTAH DAERAH KABUPATEN KARIMUN DALAM MENGELOLA SUMBERDAYA MINERAL PERTAMBANGAN GRANIT TAHUN 2014 – 2016 - Satria, Said Yasser; Anwar, Khairul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The purpose of this study is the first, to describe the managerial capabilities of the Karimun Regency government in the management of granite mining activities that are used for the benefit of the welfare of the community and the region. Secondly, to illustrate the political capability of local government in facing the existing demands in the community, to make policies and implement policies made by the local government together with the district parliament Karimun.The problem of environmental damage occurring in the mining environment is a serious problem that should be anticipated by the Regional Government, not just about environmental damage. Regional governments should also be able to manage granite mineral resources for regional economic progress. the welfare of the community and for the sake of sustainable development therefore the Theory of Regional Government Capacity which consists of; Managerial Ability and Political Ability are urgently needed.With descriptive research method using qualitative approach. The researcher describes the problems related to granite mining which are derived from observations in the field, opinions of informants and descriptive statistics.The result of the research concludes that managerial ability in management of granite mining by conducting AMDAL Planning and Sustainable Development Planning in managing granite mining has been going well. While Political Ability in granite mining management in Karimun Regency actually has strong authority is the provincial government in accordance with the law regulation No. 23 of 2014 which has the right to grant permits, supervise and others related to the management of granite mining in Karimun Regency is Riau Islands Province. However, the role of Regent related to Responsive Capability can only be proposed and reported to Riau Islands Province, because Riau Kepulaluan Province has an important role in making policy.Keywords: Managerial Ability, Political Ability